207k views
0 votes
What is the solution to the equation below? ​

What is the solution to the equation below? ​-example-1

1 Answer

2 votes

Answer:

The solutions are (2,0) and (3,0)

Explanation:

The common denominator is (x - 2)(x - 4) which comes to x^2 - 6x + 8 which is exactly what the denominator on the right hand side is.

2x (x - 4) - (x+3)(x - 2) = - 4x

============= ========

(x -2)(x - 4) x^2 - 6x - 8

Multiply both sides by x^2 -6x - 8

2x(x - 4) - (x^2 + x - 6 ) = - 4x Remove the brackets

2x^2 - 8x - x^2 - x + 6 = - 4x Combine like terms on the left

2x^2 - x^2 - 8x - x + 6 = - 4x

x^2 - 9x + 6 = - 4x Add 4x from both sides

x^2 - 9x + 4x + 6 = 0

x^2 - 5x + 6 = 0

This factors into

(x - 2) and (x - 3)

x - 2 = 0

x = 2

x - 3 = 0

x = 3

User Mcarifio
by
4.6k points